Germany : Staff Report for the 1999 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that the monetary conditions in Germany have eased significantly since late 1998, reflecting both policy actions and exchange rate developments. Short-term interest rates were reduced by the Bundesbank to 3 percent in December 1998 and, in the new context of European Monetary Union, by the European Central Bank to 2 1\2 percent in April 1999. The depreciation of the euro against other currencies since its inception in January 1999 has also been supportive of activity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet